Суб’єкти доказування в адміністративному судочинстві України - Гордєєв, Віталій Володимирович (My University, 2022)
Постановка проблеми. Становлення України як незалежної правової держави із високим пріоритетом щодо дотри-мання прав та основних свобод людини і громадянина неможливе без чіткого дотримання правил доказування в ад-міністративному судочинстві уповноваженими суб’єктами. Мета статті полягає у з’ясуванні переліку суб’єктів доказо-вої діяльності в судовому адміністративному процесі та їх процесуальної діяльності щодо доказування. Методологічну основу статті становить діалектичний метод наукового пізнання, за допомогою якого здійснено зага-льнотеоретичне дослідження поняття доказування в адміністративному судочинстві, системний метод реалізований під час вивчення суб’єктів доказування в адміністративному судочинстві, методи аналізу та синтезу були використані під час дослідження судової практики в даній сфері суспільних відносин. Результатом дослідження є з’ясування по-няття доказування в адміністративному судочинстві та переліку суб’єктів доказової діяльності. Висновки. Встанов-лено, що доказування в адміністративному судочинстві – це діяльність уповноважених суб’єктів судового адміністра-тивного процесу на збір та подання інформації про певні події, дії або стан, чи витребування судом такої інформації за клопотанням учасників справи чи їх представників, або за власною ініціативою суду для її дослідження та пода-льшої оцінки. Суб’єктами доказової діяльності в адміністративному судочинстві є суд та особи, які зацікавлені у ви-рішенні справи (сторони; треті особи; представники сторін та третіх осіб). Problem statement. The Ukraine establishment as an independent state governed by the rule of law with high priority in respecting the rights and fundamental freedoms of peoples is impossible without strict observance of the rules of evidence in administrative proceedings by authorized entities. The purpose of this article is to define the concept, content of evidence in administrative proceedings, as well as to clarify the list of subjects of evidentiary activity in judicial administrative proceedings, based on the achievements of modern legal science, current legislation and law enforcement practice. The methodological basis of the article is a dialectical method of scientific knowledge, which carried out a general theoretical study of the concept of proving in administrative proceedings, a systematic method implemented in the study of proving in administrative proceedings, methods of analysis and synthesis were used in the study of jurisprudence practice in this field. The result of the research is to clarify the concept of evidence in administrative proceedings and the list of subjects of evi-dence. Conclusions. It is established that evidence in administrative proceedings is the activity of authorized subjects of ju-dicial administrative proceedings to collect and submit information about certain events, actions or conditions, or demand such information by the court at the request of participants or their representatives, or on its own initiative research and fur-ther evaluation. The subjects of evidentiary activity in administrative proceedings are the court and persons who are inter-ested in resolving the case (parties; third parties; representatives of the parties and third parties). In administrative cases concerning appeals against decisions, actions or omissions of the subject of power, the presumption of his guilt is established. The presumption of guilt in administrative proceedings is the assumptions established by law that the circumstances of the administrative case reported by the plaintiff about the decisions, actions or omissions of the defendant (subject of authority) are true until the defendant refutes them.
Keywords: суб’єкти адміністративного судочинства; сторони; позивач; відповідач; доказування